2020
DOI: 10.30880/ijie.2020.12.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Supply Chain Disruption Risks in the Malaysian Automotive Remanufacturing Industry-a Case Study

Abstract: Remanufacturing has now become one of the effective strategies for reducing the negative impact on the environment by prolonging the products' life cycle in the automotive sector. Still considered as a relatively new industry in Malaysia, the low remanufacturing rate coupled with the lack of standardization are thus seen as causing a high inclination of disruption occurrences in the remanufacturing operations. As such, this paper had identified and investigated the existing disruptions in four problematic area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous research has showed that there are various difficulties that would have a negative impact on supply chain performance as a result of it. These challenges include buyer-supplier collaboration, chain partnership quality, customer service, supplier network performance, and information flow [27][28][29]. As a result, knowing the customer and improving the buyer-supplier connection are crucial for attaining high performance.…”
Section: Methodology 21 An Overview Of the Automotive Industry In Mal...mentioning
confidence: 99%
“…Previous research has showed that there are various difficulties that would have a negative impact on supply chain performance as a result of it. These challenges include buyer-supplier collaboration, chain partnership quality, customer service, supplier network performance, and information flow [27][28][29]. As a result, knowing the customer and improving the buyer-supplier connection are crucial for attaining high performance.…”
Section: Methodology 21 An Overview Of the Automotive Industry In Mal...mentioning
confidence: 99%
“…This study adopted the CA method for critical literature review to draw the essential points of the issues raised related to the supply chain. Ropi et al (2020) analysed the problematic areas in mitigating the different risks encountered by Malaysian automobile remanufacturers and determined the appropriate steps to resolve the interruptions and challenges in remanufacturing the supply chain system. Masoumi et al (2019) presented a process-oriented systematic review to deal with the automotive industry's sustainable supply chain management issues.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that the automobile industry and ELV recycling system are potentially intertwined [58], they are not working together and collaborating. For the dismantling and other subsequent operations, the ELV dismantler needs accurate and valuable information from the manufacturers.…”
Section: Different Value Chainmentioning
confidence: 99%